2020
DOI: 10.1101/2020.05.06.080382
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neutral sphingomyelinase 2 regulates inflammatory responses in monocytes/macrophages induced by TNF-α

Abstract: Obesity is associated with elevated levels of TNF-α and proinflammatory CD11c monocytes /macrophages. TNF-α mediated dysregulation in the plasticity of monocytes/macrophages is concomitant with pathogenesis of several inflammatory diseases, including metabolic syndrome, but the underlying mechanisms are incompletely understood. Since neutral sphingomyelinase 2 (nSMase2; product of the sphingomyelin phosphodiesterase 3 gene, SMPD3) is a key enzyme for ceramide production involved in inflammation, we investigate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This made them attractive drug targets exemplified by the anti‐inflammatory effects of sphingomyelin synthase 2 inhibition. Although the inhibition of sphingomyelin synthesis has been shown to reduce TLR4 signalling, targeting neutral sphingomyelinases catalysing the conversion of sphingomyelin to ceramide equally shows a reduced pro‐inflammatory phenotype in macrophages (Al‐Rashed et al, 2020; Amtmann et al, 2003) with a beneficial effect in sepsis (Anderson et al, 2012; Essandoh et al, 2015). This suggests that targeting both sphingomyelin production and conversion to ceramide can exert anti‐inflammatory effects in macrophages, possibly through distinct mechanisms that remain to be identified.…”
Section: Therapeutic Implications and Concluding Remarksmentioning
confidence: 99%
“…This made them attractive drug targets exemplified by the anti‐inflammatory effects of sphingomyelin synthase 2 inhibition. Although the inhibition of sphingomyelin synthesis has been shown to reduce TLR4 signalling, targeting neutral sphingomyelinases catalysing the conversion of sphingomyelin to ceramide equally shows a reduced pro‐inflammatory phenotype in macrophages (Al‐Rashed et al, 2020; Amtmann et al, 2003) with a beneficial effect in sepsis (Anderson et al, 2012; Essandoh et al, 2015). This suggests that targeting both sphingomyelin production and conversion to ceramide can exert anti‐inflammatory effects in macrophages, possibly through distinct mechanisms that remain to be identified.…”
Section: Therapeutic Implications and Concluding Remarksmentioning
confidence: 99%
“…Sphingomyelin is cleaved by sphingomyelinases to produce ceramide which induces a signaling cascade that can lead to the differentiation, proliferation, apoptosis, or cytokine secretion by select immune cell populations. It was recently shown that neutral sphingomyelinase 2 can cause monocyte migration and secretion of inflammatory cytokines in response to soluble TNF-α 142 . Elevated TNF-α has been associated with both obesity and severe cases of COVID-19 143 .…”
Section: Monocytementioning
confidence: 99%
“…29 NSM-2 was, furthermore, shown to be involved in endothelial activation and monocyte recruitment as well as monocyte activation. 30,31 Interestingly, NSM-2 is also involved in the biogenesis of extracellular vesicles, 32 which are important mediators of endothelial-cell function and atherosclerotic plaque development. 33,34 In the context of extracellular vesicles, our group showed that hyperglycemia-induced activation of NSM-2 promotes endothelial apoptosis through the intercellular transfer of ceramides via extracellular vesicles.…”
Section: Ceramide Metabolismmentioning
confidence: 99%